Expert podcasting practices for dummies - Morris, Tee, 1968- (--For dummies., 2008)
A guide to audio and video podcasting covers such topics as developing a podcast, podcasting equipment and tools, recording a podcast, encoding software, the video and audio editing process, getting listed in podcast directories, the podcast community, and making money with podcasting.